An Investigation of the Quantitative Correlation between Urban Spatial Morphology Indicators and Block Wind Environment - Di Wei; Xing Hu; Yangjun Chen; Baofeng Li; Hong Chen (Atmosphere, 2021)
The research purpose of this work is guiding the spatial morphological design of blocks via relevant indicators to realize suitable wind environments. In doing so, it is necessary to find the most suitable indicator types and value ranges for each urban spatial morphology. At present, most of the relevant research has been based on the numerical simulation of ideal block shapes and rarely proposes results based on actual block types, which often tend to be complex environments. Therefore, this paper firstly presents a theoretical speculation on the main factors influencing indicator effectiveness via analyzing physical significance and formulating principles for each indicator. These speculations are verified via wind environment measurement and statistical analysis, indicating that porosity (P0) can be used as an important indicator to guide the design of block wind environments in the case of deep street canyons, while frontal area density (λF) can be used as a supplement in shallow street canyons with no height differences. Finally, computational fluid dynamics (CFD) is used to quantify the impact of block height difference and street canyon depth on λF and P0, thereby finding suitable types of urban form and value ranges for λF and P0. This paper provides a feasible wind environment index system for urban designers.